2022
DOI: 10.1002/agm2.12232
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential neuroprotective compound from Ganoderma lucidum extract targeting microtubule affinity regulation kinase 4 involved in Alzheimer's disease through molecular dynamics simulation and MMGBSA

Abstract: Objective: Alzheimer's disease (AD) is one of the most prevalent neurological ailments, affecting around 50 million individuals globally. The condition is characterized by nerve cell damage due to the formation of amyloid-beta plaques and neurofibrillary tangles. Only a few US Food and Drug Administration (FDA)-approved medications are available in the market which are devoid of side effects, thus, making it imperative to investigate new alternatives for countering this disease. According to a recent study, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…et al; 2021 found out that irisin; (a protein that plays a vital role in memory dysfunction in AD) binds with MARK4 and maintains stability [30]. Most recent data indicates that ganoderic acid A and ganoderenic acid B are the most promising molecules derived from Ganoderma lucidium that bind with MARK4 [31]. Previous research supports our study, and ebelin lactone is considered the most promising neuroprotective compound from the Bacopa monnieri extract, which binds with MARK4.…”
Section: Discussionsupporting
confidence: 83%
“…et al; 2021 found out that irisin; (a protein that plays a vital role in memory dysfunction in AD) binds with MARK4 and maintains stability [30]. Most recent data indicates that ganoderic acid A and ganoderenic acid B are the most promising molecules derived from Ganoderma lucidium that bind with MARK4 [31]. Previous research supports our study, and ebelin lactone is considered the most promising neuroprotective compound from the Bacopa monnieri extract, which binds with MARK4.…”
Section: Discussionsupporting
confidence: 83%
“…Bacosides isolated from Brahmi, are non polar glycosides in nature and they easily cross the blood brain barrier [42][43][44]. This has been confirmed by radiopharmaceuticals biodistribution studies [45]. Thus, the Brahmi, rich in Bacosides have potent neuroprotective potentials and may be explored for utilizing the phytocompounds as lead molecules for developing more potent and effective neuroprotective drugs.…”
Section: Neuroprotective Compounds From Bacopa Monnieri (Brahmi)mentioning
confidence: 79%
“…The user has provided a numerical reference [ 28 ]. According to recent investigations [ 29 ], the molecules ganoderic acid A and ganoderenic acid B, produced from Ganoderma lucidium, have shown significant potential in their interaction with MARK4. According to the latest investigation, galantamine has been identified as a potentially effective inhibitor for MARK 4 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%